Trifluralin Toxicology Revisited: Microtubule Inhibition, Mitochondrial Damage, and Anti-Protozoan Potential - Darío Lirussi (Future Pharmacology, 2025)
The aim of this review is to evaluate the therapeutic possibilities of trifluralin and other 2,6-dinitroaniline herbicides by assessing different aspects of trifluralin’s toxicology (including its mitochondrial toxicity), pharmacokinetics, and environmental fate. The particular features of TFL have triggered a wide range of policies about its properties. Is has been banned in some countries and, at the same time, has been proposed as a drug for the cure of parasitic disease by some scientific research articles. The use of this pre-emergence herbicide to control broadleaf weeds and annual grasses is assumed to rely only on its microtubule depolarization or cytoskeleton disassembly abilities (on-target effect), a fact that justifies its inhibition of a wide range of microorganisms (mostly protozoans), sharing a relatively high degree of conservation in tubulin protein sequences with weeds and grasses. Recent studies have confirmed that TFL also affects mitochondrial function (off-target effect), a hypothesis previously suggested in earlier works. Here, we account for the main issues in TFL toxicology, other potential uses of the herbicide outside crops, and its feasibility for use as an antiprotozoal drug.